ORBITAL TRAJECTORY SIMULATION ON TWIN STARS SYSTEM IN IFS FRACTAL MODEL BASED ON HYBRID ANIMATION METHOD - Tedjo Darmanto; Iping Supriana Suwardi; Rinaldi Munir (Faculty of Computer Science - Universitas Indonesia, 2015)
IFS (Iterated Function Systems) is a method to model fractal object based on affine transformation functions. The star-like object rotation effect in the IFS fractal model could be exhibited by using metamorphical method, as a replacement to the affine rotation method on a non metamorphic animation. The advantage of a metamorphic animation method over the metamorphic animation method is that the object's relative position to the fixed point as an absolute centroid is absolute. Therefore, the rotational effect can be exhibited at any positions. In addition, it can also be combined with rotational effect of the local centroid itself around the absolute centroid as a fixed point by the primitive rotational operation to form an interesting behavior of orbital trajectory Based on the hybrid of both animation methods, the animation simulation could be done on orbital trajectory on a twin stars rotating to each other as a system. Both objects are rotated in the same angular direction, but started in the opposite position around two closely different fixed points. So, the orbital trajectory yielded forms an elliptical path. The two similar objects can be created efficiently by cloning-scaling technique. In general, the animation method can be modeled as an animation framework.